Ischemic Stroke in Patients With Sinus Node Disease, Atrial Fibrillation, and Other Cardiac Conditions. Issue 6 (June 2020) - Bodin, Alexandre; Bisson, Arnaud; Gaborit, Christophe; Herbert, Julien; Clementy, Nicolas; Babuty, Dominique; Lip, Gregory Y.H.; Fauchier, Laurent
Abstract : Background and Purpose—: Atrial fibrillation (AF) is known to increase risk of ischemic stroke (IS), but the risk of IS in isolated sinus node disease (SND) is unclear. We compared the incidence of IS in patients with SND, patients with AF, and in a control population with other cardiac diseases (disease of the circulatory system using the International Classification of Diseases, Tenth Revision ). Methods—: This French longitudinal cohort study was based on the national database covering hospital care for the entire population from 2008 to 2015. Results—: Of 1 692 157 patients included in the cohort, 100 366 had isolated SND, 1 564 270 had isolated AF, and 27 521 had AF associated with SND. Incidence of IS during follow-up was higher in isolated patients with AF than in AF associated with SND (yearly rate 2.22% versus 2.06%) and in isolated patients with AF than in isolated patients with SND (yearly rate 2.22% versus 1.59%). The incidence of IS was lower in a control population with other cardiac conditions (n=479 108) compared with SND and patients with AF (0.96%/y, 1.59%/y, and 2.22%/y, respectively). After 1:1 propensity score matching, SND was associated with lower incidence of IS compared to AF (hazard ratio, 0.77 [95% CI, 0.73–0.82]) but higher incidence of IS compared to control population (hazard ratio, 1.27 [95%CI, 1.19–1.35]). Conclusions—: Patients with SND had a lower risk of thromboembolic events than patients with AF but a higher risk than a control population with other cardiac diseases. Randomized clinical trial in a selected SND population, with, for example, a high CHA2 DS2 -VASc score, would be required to determine the value of IS prevention by anticoagulation. Abstract : Supplemental Digital Content is available in the text.